Watch us shine : a novel - De los Santos, Marisa, 1966- (William Morrow, an imprint of HarperCollinsPublishers, 2023)
"Cornelia Brown is reeling from a terrifying act of violence when she gets word that her mother has been badly injured in an accident. Cornelia returns to Virginia, to the house she grew up in, and in the weeks that follow, she watches her mother Ellie struggle to recover, fluctuating between her usual crisp, can-do clarity and periods of delirium during which she seems haunted by a devastating loss from her past. In grief-stricken tones, Ellie begs Cornelia to bring her the northern lights, and despite her confusion at this mysterious plea, Cornelia vows to do so: 'She was my mother and she wanted the Northern Lights; I was her daughter and would have given her anything, anything.' With the help of her prickly sister, Ollie, Cornelia embarks on a mission to piece together the lost years of their mother's life: people, places, and events spanning Ellie's late teens through her mid-twenties. Cornelia and Ollie's quest takes them to unexpected places and into the worlds of strangers whose lives Ellie touched and irrevocably changed. As the sisters uncover truths about their mother's life--some beautiful, some ugly, some tragic--Cornelia herself begins to heal, to forgive herself, and to find her way back home"--Dust jacket flap.